Innovative Behavior in The Health Sector During the Covid-19 Pandemic: A Moderated- Mediated Perspective - Putri, Melisa Ariani; Johannes, Johannes; Rosita, Sry (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The Covid-19 pandemic has forced rapid changes. To support this acceleration of change, employees' innovative behavior is essential. Innovative behavior serves as a construct for generating ideas and implementing them. This study aims to develop a model of innovative behavior influenced by job design, with a moderating perspective of knowledge sharing and a mediating perspective of intrinsic motivation. The sample in this study consists of 258 respondents, with data analysis techniques using SEM-PLS and WarpPLS 7.0. The findings indicate that job design has a significant positive effect on intrinsic motivation, knowledge sharing, and employees' innovative behavior. Intrinsic motivation serves as a mediator, influencing the indirect relationship between job design and innovative behavior, partially mediating this relationship. Meanwhile, knowledge sharing as a moderator strengthens the relationship between job design and innovative behavior among employees. This suggests that knowledge exchange among employees generates information related to the pandemic, facilitating opportunities and changes through creative solution concepts that promote and implement their innovative ideas in the workplace.